2023
DOI: 10.4082/kjfm.22.0142
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Smoking Cessation of Heated Tobacco Product Users and Conventional Cigarette Smokers in Korea

Abstract: Background: Since the introduction of heated tobacco products (HTPs) in Korea in 2017, their annual sales have increased. Several studies have investigated the perceptions of HTPs and smoking cessation behaviors. For the first time, In 2019, questions focused on HTP use were introduced in the Korea National Health and Nutrition Examination Survey (KNHNES). This study aimed to compare smoking cessation behaviors between HTP users and conventional cigarette smokers using KNHANES data.Methods: Data of 947 current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Current smokers can be categorized into three tobacco use categories: exclusive combustible cigarette users, exclusive heated tobacco product (HTP) users, and dual (combustible cigarette and HTP) users [9,10]. A previous study has shown that HTP users are less likely to want to quit smoking [11]. Despite the importance of considering the use of HTPs when studying smokers who want to quit, there is limited research that focuses on this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Current smokers can be categorized into three tobacco use categories: exclusive combustible cigarette users, exclusive heated tobacco product (HTP) users, and dual (combustible cigarette and HTP) users [9,10]. A previous study has shown that HTP users are less likely to want to quit smoking [11]. Despite the importance of considering the use of HTPs when studying smokers who want to quit, there is limited research that focuses on this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…In the present issue, Won et al [ 6 ] compared the intention to quit smoking within 6 months and quitting attempts in the past year among CC-only smokers, HTP-only smokers, and dual users of CCs and HTPs, using data from the eighth Korea National Health and Nutrition Examination Survey (KNHANES VIII-1), 2019. The study participants included 947 adults who smoked CCs or HTPs daily.…”
mentioning
confidence: 99%